Do consumer shopping styles influence consumer attitudes toward services offered by shopping websites?. Issue 1 (1st January 2016) - Khare, Arpita; Khare, Anshuman; Mukherjee, Sourjo; Goyal, Tanuj
ABSTRACT: The purpose of the current research was to examine the influence of consumer shopping styles on Indian consumers' attitude toward services offered by shopping websites. Online service factors like product information, refunds, transactions, ability to return and exchange products, ability to cancel orders, and customer support services were examined. Unlike research findings from other countries, it was found that different consumer styles had no influence on consumers' online service attitude. Only a quality-conscious shopping style influenced consumers' website service attitude. The findings can help online shopping firms and retailers in understanding fears and apprehensions of consumers regarding online service. Service-related factors like refunds, product delivery, information availability, customer service, and financial transactions can be modified to improve consumers' attitudes toward online shopping websites. Future research can address issues related to consumer attitudes toward website features, layout, design, displays, and pictorial images.